Th1 Platform Immune Responses Against Leishmania major Induced by Thiol-Specific Antioxidant-Based DNA Vaccines - Tabatabaie, Fatemeh (Kowsar, 2014)
BACKGROUND: The Thiol-specific antioxidant (TSA) is an antigen of Leishmania major which is believed to be the most promising molecule as a vaccine candidate against leishmaniasis. OBJECTIVES: In this study, we investigated the protective efficacy of TSA-based DNA vaccine against L. major infection. MATERIALS AND METHODS: Recombinant plasmid construction TSA (pcTSA) was prepared and transfected into eukaryotic cells and expression was confirmed with western blot and RT-PCR. The mice were assigned to six different groups and DNA immunization was performed with 100 µg intramuscular recombinant plasmid with a two-week interval. Cytokines and lymphocyte proliferation assay, antibody responses and determination of parasite burden were performed following immunization and the challenging infection with L. major. RESULTS: The antibody and IFN-γ titers were higher in pcTSA + AlPO4 group the immunized mice with pcTSA alone, but there was no statistically significant difference between the two groups. Additionally the IL-4 titer was not statistically different between the groups following immunization and challenge. After infection with L. major promastigotes, the immunized mice with pcTSA and the one immunized with both pcTSA + AlPO4 presented a considerable reduction in diameter of lesion but there was no statistical difference between the two groups. The immunized mice had significantly lower parasite loads. No significant differences were observed between the two vaccinated groups. However the highest reduction in parasite burden was observed in the group immunized with pcDNA + AlPO4. No significant differences were observed in survival rate of the immunized mice after the challenge with L. major. CONCLUSIONS: In conclusion, TSA-based DNA vaccine induced Th1 platform immune response and aluminum phosphate could improve the efficacy of these vaccines with induction of humoral and cellular immune responses against L. major infection. There were no significant differences observed between pcTSA and pcTSA + AlPO4 groups.